The relationship between malaria parasitaemia and availability of healthcare facility in Mpwapwa District, central Tanzania - Mboera, LEG; Kamugisha, ML; Rumisha, SF; Msangeni, HA; Barongo, V; Molteni, F; Kitua, AY (Tanzania Journal of Health Research, 2006)
A study was carried out in six villages located at different altitudes in Mpwapwa district of central Tanzania to determine malaria parasitaemia and transmission levels in villages with or without health care facilities. A total of 1119 schoolchildren (age= 5.9-12.3 years) were examined for malaria parasitaemia. Plasmodium falciparum was the predominant malaria species accounting for 92.8% of all species. The average malaria prevalence rate among schoolchildren was 25.8% (range 1.5-53.8%). The geometric mean parasite densities for P. falciparum was 361 (N= 286). Higher malaria prevalence was observed in villages at lower (<1000 m) than at intermediate (1000-1500m) or higher (>1500m) altitudes. Schoolchildren in areas with health care facilities were less at risk of acquiring malaria by 33.4% as compared with those living in areas without health facilities. Mean packed cell volume in schoolchildren was 38.5% (range= 35.2-41.0%). Splenomegaly was observed in 18.1% (0-40.2%) of the schoolchildren examined and it was higher among those in villages without health care facilities. Anopheles gambiae sensu lato was the only malaria vector found in the district and was found in all villages and at all altitudes. Sporozoite rate in An. gambiae s.l. ranged from 0-10.5%, with the lowland villages recording the highest rates. This study indicates that altitude and geographical accessibility to healthcare service are important determinants of malaria infection among rural communities in Tanzania. Keywords: malaria, schoolchildren, altitudes, health care facility, Tanzania Tanzania Health Research Bulletin Vol. 8(1) 2006: 22-27